2014
DOI: 10.4269/ajtmh.13-0714
|View full text |Cite
|
Sign up to set email alerts
|

A Door-to-Door Survey of Bed Bug (Cimex lectularius) Infestations in Row Homes in Philadelphia, Pennsylvania

Abstract: Abstract. We conducted a door-to-door survey in a residential census tract of Philadelphia to estimate the prevalence and spatial patterns of recent bed bug infestations. We interviewed 596 residents, of whom 66 (11.1%) reported recent bed bug infestations. We confirmed current infestations in a subset of 15 (68.2%) of 22 inspected households. Most residents reported that their infestation began within the past year (2012)(2013). We found no correlation between property value and infestation status. Spatial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…The common bed bug, Cimex lectularius L. (Hemiptera: Cimicidae), has become a common pest in low-income housing in North America in recent years. [1][2][3][4][5] Unlike other common household pests, bed bug bites can cause itchiness, pain, anxiety, sleep loss, social ostracism, delusional parasitosis, and stress. [6][7][8][9] Professional bed bug control service typically costs at least US $500 per infestation and often fails to completely eradicate the bed bugs.…”
Section: Introductionmentioning
confidence: 99%
“…The common bed bug, Cimex lectularius L. (Hemiptera: Cimicidae), has become a common pest in low-income housing in North America in recent years. [1][2][3][4][5] Unlike other common household pests, bed bug bites can cause itchiness, pain, anxiety, sleep loss, social ostracism, delusional parasitosis, and stress. [6][7][8][9] Professional bed bug control service typically costs at least US $500 per infestation and often fails to completely eradicate the bed bugs.…”
Section: Introductionmentioning
confidence: 99%
“…Bed bugs (Cimex lectularius L.) (Hemiptera: Cimicidae) remain one of the most challenging pests to manage indoors. Since their resurgence in the early 2000s, infestations have been documented from across the globe (Doggett et al 2004, How and Lee 2010, Levy Bencheton et al 2011, Potter 2011, Wang and Wen 2011, Faúndez and Carvajal 2014, with high infestation rates especially frequent in low-income communities (Wu et al 2014, Wang et al 2016. Bed bugs affect humans physically (bites) (Goddard and deShazo 2009), psychologically de Shazo 2012, Susser et al 2012), and they produce copious amounts of histamine that may trigger allergies and asthma (DeVries et al 2018).…”
mentioning
confidence: 99%
“…A meta-analysis study of the bed bug infestation (Cimex lectularius) in Iran during 1995-2019 reported the weighted mean of this infestation was estimated 0.28 (18). A door-to-door survey showed 11.1% of Cimex lectularius infestations in row homes in Philadelphia, Pennsylvania (19). The bed bug infestation was reported 21.8% in Benue State in Nigeria (20).…”
Section: Discussionmentioning
confidence: 99%